(untitled) (World Science, 2018)
The article presents the operating principle of atmospheric gravitational converter (hereinafter referred to as AGT) with an external supply of non-thermal clean energy. The operating principle is based on using the existing potential energy of the atmosphere in the gravitational field of the Earth. AGK is characterized by unique capabilities to generate by implosion useful clean energy without harmful emissions, such as NОх and СО2. Its main advantage is that the supply of external non-thermal energy for the operation of AGK is carried out steadily in any required quantity and is not dependent on the time of day, weather or location.